Detection of Fusarium spp. and T-2 and HT-2 toxins contamination in oats using visible and near-infrared spectroscopy - Teixido-Orries, Irene; Yang, Lexuan; Molino, Francisco; Medina, Angel; Marín, Sonia; Verheecke-Vaessen, Carol (Elsevier, 2025)
Fusarium langsethiae (FL) is one of the major contaminants in oats in the United Kingdom (UK) and is a significant producer of T-2 and HT-2 toxins, among the most prevalent mycotoxins in oats. Visible and near-infrared (Vis-NIR) (350–2500 nm) spectroscopy was explored as a non-invasive, rapid method for detecting FL, Fusarium species that produce T-2 and HT-2 toxins, and T-2 and HT-2 toxins content. Oat grains were artificially inoculated with FL and other Fusarium species under controlled water activity (aw) conditions (0.98, 0.90, and 0.80). FL was found to be particularly responsible for producing T-2 and HT-2 toxins. Classification models were developed to distinguish oat grains based on the presence of FL. The best performance was achieved with all the Vis-NIR spectra, with a classification accuracy of 76.2 %. The Vis region (350–995 nm) emerged as the most important range for classification. Additionally, oat grains were classified by T-2 and HT-2 toxin content, distinguishing oats above and below the European Union (EU) threshold with 93.3 % accuracy. For mycotoxin quantification, the best performance was obtained using the Vis region with a coefficient of determination (R2) of 0.875. Key wavelengths such as 464, 568, 575 and 636 nm were relevant for toxin detection. The NIR region (1005–1795 nm) also played a significant role in the models. This study shows that Vis-NIR spectroscopy is a promising, non-destructive tool for detecting Fusarium and type A trichothecenes in oats, though further research is needed to improve model robustness and support food safety monitoring.
Keywords: Applied mycology; Fungal contamination; Fusarium langsethiae; HT-2 toxin; Mycotoxin detection; Oat; T-2 toxin; Vis-NIR spectroscopy; Microbiology